2015
DOI: 10.1007/s10236-015-0808-z
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of ensemble-based assimilation of satellite altimetry and tide gauge data in storm surge prediction

Abstract: Cyclogenesis and long-fetched winds along the southeastern coast of South America may lead to floods in populated areas, as the Buenos Aires Province, with important economic and social impacts. A numerical model (SMARA) has already been implemented in the region to forecast storm surges. The propagation time of the surge in such extensive and shallow area allows the detection of anomalies based on observations from several hours up to the order of a day prior to the event. Here, we investigate the impact and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In particular, the total water level envelope (i.e., the SSH anomaly including tides and barometric effects) was used to allow direct comparison with in-situ measurements. Richter et al (2012), Etala et al (2015), and Lago et al (2017) showed that the altimetry data uncertainty in the SWACS depends upon the distance to the shoreline, and ranges between 0.02 and 0.30 m. Therefore, following the results reported by Etala et al (2015), an uncertainty of 0.15 m was assigned to them.…”
Section: Altimetry and Tidal Gauges Observationsmentioning
confidence: 73%
See 3 more Smart Citations
“…In particular, the total water level envelope (i.e., the SSH anomaly including tides and barometric effects) was used to allow direct comparison with in-situ measurements. Richter et al (2012), Etala et al (2015), and Lago et al (2017) showed that the altimetry data uncertainty in the SWACS depends upon the distance to the shoreline, and ranges between 0.02 and 0.30 m. Therefore, following the results reported by Etala et al (2015), an uncertainty of 0.15 m was assigned to them.…”
Section: Altimetry and Tidal Gauges Observationsmentioning
confidence: 73%
“…(2017) showed that the altimetry data uncertainty in the SWACS depends upon the distance to the shoreline, and ranges between 0.02 and 0.30 m. Therefore, following the results reported by Etala et al . (2015), an uncertainty of 0.15 m was assigned to them.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence the ensemble serves both to forecast the uncertainty as well as improve the central forecast. Etala et al (2015) report advances in storm surge forecasting for the Argentian coast. Using a Local Ensemble Transform Kalman Filter (LETKF), water level from in situ gauges and satellite altimetry is assimilated into a high-resolution 20-member ensemble storm surge model.…”
Section: The 13th Workhopmentioning
confidence: 99%